Biaryl thioether synthesis via CuI catalyzed dominothiolation of aryl halides in the presence of DMAP as ligand. Issue 19 (6th May 2015) - Roy, Subhasish; Phukan, Prodeep
Graphical abstract: Highlights: A faster method for the synthesis of biaryl thioethers from aryl halides. Use of DMAP as ligand for CuI catalyzed C–S cross coupling reaction. Significant rate acceleration of CuI catalyzed process by DMAP. Applicable to different kinds of aryl iodides and bromides. The product yields are high. Abstract: An improved protocol has been developed for the synthesis of symmetrical biaryl sulfides via a dominothiolation reaction using CuI as catalyst in the presence of DMAP as ligand. The coupling reaction of aryl halides was carried out in the presence of 5 mol % of CuI and 20 mol % of DMAP using thiourea as sulfur transfer agent. High yields of corresponding product were obtained by carrying out the reaction in DMSO at 120 °C.